MACROANATOMICAL STRUCTURE OF THE PANCREAS - Student: Allambergenova Jasmina; Scientific Supervisor: Niyozov Norbek (The Conference Hub, 2025)
This article discusses the anatomical and physiological structure of the pancreas, its role in the digestive and endocrine systems, as well as the causes and consequences of pancreatic dysfunction. The pancreas is one of the most important mixed glands in the human body. Through the production of digestive enzymes, it participates in the process of digestion, while through the secretion of insulin and other hormones, it regulates metabolism.
Keywords: pancreas, pancreatitis, insulin.